FEATURES OF THE IMPLEMENTATION OF THE LAW OF UKRAINE «ON EDUCATION» - Holovko, Svitlana H. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
Purpose: the adoption of the Law of Ukraine "On Education", which is a systematic element of modern domestic legislation in the education area, has become an important step towards the formation of the legal framework for the functioning of all educational levels. One of the most urgent problems of this process is ensuring effective implementation of the new law. In its turn, it actualizes the study of the peculiarities and practical tools for the implementation of the basic legislative norms as an important condition for the basic law efficiency. Methods: to fulfill the research tasks general scientific and special methods of legal science have been applied. By means of the formal-logical method, the basic norms of the current legislation on education were analyzed, and the basic role of the law "On Education" was grounded. Applying the comparative legal method made it possible to note the Europeanisation of normative and legal support of the domestic educational industry and to determine the features of its implementation. Results: peculiarities of the formation and introduction of normative and legal support for the functioning of the domestic education system are analyzed. The compliance of the norms of the modern legislation on education with the European tendencies is argued. The most actual practical steps that will promote effective implementation of the Law of Ukraine "On Education" are underscored. Discussion: an important feature of the new basic law in the education area is the availability of independent norms and transitional provisions. Correspondingly, the further research is required by the harmonization of domestic legislation on education, the definition of the primary components of the legal and regulatory framework, which require development, harmonization of existing normative acts, the development of a system of measures to involve the general public in this process.